2020
DOI: 10.3389/feart.2020.562548
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Behaviour, Wear and Comminution of Synthetic Porous Geomaterials

Abstract: During shearing in geological environments, frictional processes, including the wear of sliding rock surfaces, control the nature of the slip events. Multiple studies focusing on natural samples have investigated the frictional behaviour of a large suite of geological materials. However, due to the varied and heterogeneous nature of geomaterials, the individual controls of material properties on friction and wear remain unconstrained. Here, we use variably porous synthetic glass samples (8, 19 and 30% porosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
(162 reference statements)
0
0
0
1
Order By: Relevance
“…Namiki, A et al [36] measured the rheology and strength of high porosity rhyolitic magma at 500-950 degrees C, measurements show that the elastic energy originated by deformations avoids attenuation and is stored in the bubbly magma until released by fracturing. Hughes, A et al [37] use variably porous synthetic glass samples (8,19, and 30% porosity) to explore the frictional behavior and development of wear in geomaterials at low normal stresses (≤1 MPa), it was concluded that the porosity of the material, and the resulting coefficient of friction, work, and wear rate, can influence slip dynamics in events such as shallow crustal faults or mass movements. Mineo, S et al [38] prediction of rock porosity through infrared thermography for non-destructive testing procedures for natural stones and prediction equations were developed from statistical analysis, establishing a standardized, non-destructive, and quick alternative to the common procedures currently used in the laboratory for measuring porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Namiki, A et al [36] measured the rheology and strength of high porosity rhyolitic magma at 500-950 degrees C, measurements show that the elastic energy originated by deformations avoids attenuation and is stored in the bubbly magma until released by fracturing. Hughes, A et al [37] use variably porous synthetic glass samples (8,19, and 30% porosity) to explore the frictional behavior and development of wear in geomaterials at low normal stresses (≤1 MPa), it was concluded that the porosity of the material, and the resulting coefficient of friction, work, and wear rate, can influence slip dynamics in events such as shallow crustal faults or mass movements. Mineo, S et al [38] prediction of rock porosity through infrared thermography for non-destructive testing procedures for natural stones and prediction equations were developed from statistical analysis, establishing a standardized, non-destructive, and quick alternative to the common procedures currently used in the laboratory for measuring porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Определить величину диссипативного нагрева в природных метаморфических системах удается достаточно редко [Mako, Caddick, 2018]. Примерами геологических объектов, в которых установлен вклад диссипативного тепла, являются Лепонтийский гнейсовый купол [Burg, Gerya, 2005], разлом в метаморфическом поясе Санбагава, Япония [Mori et al, 2015], мусковит-биотитовые лейкограниты Армориканской сдвиговой зоны [Strong, Hanmer, 1981], лейкограниты Главного Гималайского надвига [Nabelek et al, 2010], интрузии гранитов и монцонитов в сдвиговой зоне разлома Айлао-Шань -Рэд Ривер (Китай -Вьетнам) [Leloup et al, 1999;Izokh et al, 2004]. Оценки температурных аномалий за счет тепла трения при сдвиге составляют 100 °С (до ~700 °С) в зоне вертикального разлома при 5-6 кбар [Strong, Hanmer, 1981] и достигают условий плавления гранита (700-800 °С) на глубине 20-40 км при пологом надвиге [Nabelek et al, 2010].…”
Section: Introductionunclassified